Exome and genome sequencing for pediatric patients with congenital anomalies or intellectual disability: an evidence-based clinical guideline of the American College of Medical Genetics and Genomics (ACMG) - Manickam, Kandamurugu; McClain, Monica R.; Demmer, Laurie A.; Biswas, Sawona; Kearney, Hutton M.; Malinowski, Jennifer; Massingham, Lauren J.; Miller, Danny; Yu, Timothy W.; Hisama, Fuki M. (Genetics in medicine, 2021)
Purpose To develop an evidence-based clinical practice guideline for the use of exome and genome sequencing (ES/GS) in the care of pediatric patients with one or more congenital anomalies (CA) with onset prior to age 1 year or developmental delay (DD) or intellectual disability (ID) with onset prior to age 18 years. Methods The Pediatric Exome/Genome Sequencing Evidence-Based Guideline Work Group ( n = 10) used the Grading of Recommendations Assessment, Development and Evaluation (GRADE) evidence to decision (EtD) framework based on the recent American College of Medical Genetics and Genomics (ACMG) systematic review, and an Ontario Health Technology Assessment to develop and present evidence summaries and health-care recommendations. The document underwent extensive internal and external peer review, and public comment, before approval by the ACMG Board of Directors. Results The literature supports the clinical utility and desirable effects of ES/GS on active and long-term clinical management of patients with CA/DD/ID, and on family-focused and reproductive outcomes with relatively few harms. Compared with standard genetic testing, ES/GS has a higher diagnostic yield and may be more cost-effective when ordered early in the diagnostic evaluation. Conclusion We strongly recommend that ES/GS be considered as a first- or second-tier test for patients with CA/DD/ID.